2013
DOI: 10.1371/journal.pone.0070205
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Morphology, Body Posture and Standing Balance Characteristics of Adolescent Able-Bodied and Idiopathic Scoliosis Girls

Abstract: The purpose of this study was to determine how pelvic morphology, body posture, and standing balance variables of scoliotic girls differ from those of able-bodied girls, and to classify neuro-biomechanical variables in terms of a lower number of unobserved variables. Twenty-eight scoliotic and twenty-five non-scoliotic able-bodied girls participated in this study. 3D coordinates of ten anatomic body landmarks were used to describe pelvic morphology and trunk posture using a Flock of Birds system. Standing bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
1
16
0
1
Order By: Relevance
“…They concluded that differences in initial pelvic alignment and pelvic motion are dependent on the level of the spinal deformity. Furthermore, pelvic distortion is well correlated with Cobb angle progression [33] in moderate untreated scoliosis. However, these studies made use of skin surface markers, and measurements were taken at a set instance as in any crosssectional study.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…They concluded that differences in initial pelvic alignment and pelvic motion are dependent on the level of the spinal deformity. Furthermore, pelvic distortion is well correlated with Cobb angle progression [33] in moderate untreated scoliosis. However, these studies made use of skin surface markers, and measurements were taken at a set instance as in any crosssectional study.…”
Section: Discussionmentioning
confidence: 90%
“…This statistical analysis method was previously used as a classification and data structure detection technique to identify the role of pelvic morphology, posture, and standing balance in moderate and severe scoliosis before bracing [33]. This is achieved by extracting the maximum variance from the data by means of orthogonal components called PCs.…”
Section: Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…For adolescents with idiopathic scoliosis, Nault et al. (2002) and Stylianides et al. (2013) found that standing imbalance was related to altered body posture parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Das Ausmaß wurde hier mit dem "sacro-femoropubic angel" bestimmt [1]. Die Beckenmorphologie bei Jugendlichen mit idiopathischer Skoliose in der frühen Adoleszenz zeigt deutliche Unterschiede zu Jugendlichen ohne Skoliose [18]. In ihrer anatomischen Studie untersuchten Boulay et al [19]…”
Section: Preece At Al [4] Schlossen Aus Diesenunclassified